Implantação do Centro de Equivalência Farmacêutica da Unidade de Farmacologia Clínica - UFC - Lima, Francisco Arnaldo Viana (2006)
The consolidation of the generic medicine market in Brazil represents important governmental strategy, a time that will mean greater access of the population to medicines. The Law nº 9,787, of 10 of February of 1999, it established the legal bases for the institution of the generic medicine in the Country. The laboratories equivalence pharmaceutical make the verification between two medicines that the same therapeutically active molecule contains, in the same amount and pharmaceutical form, being able or not to contain identical excipient, if vitro is equivalents in. The Centers of Equivalence Pharmaceutical must be qualified visor ANVISA, that is, they are evaluated by General Office of Laboratories of Public Health (GGLAS), second determined parameters, starting to be part of Brazilian Net of Analytical Laboratories in health (REBLAS) and being, from now on, authorized for the accomplishment of the studies equivalence pharmaceutical. (In this context it is that the following methodology was implemented the Pharmaceutical equivalence Laboratory of the UNIFAC having followed: Physical infrastructure and adequacy of the laboratory; Qualification and calibration of devices equipment; Validation of Analytical Methods; Preparation of Operational Procedures Standard (POP) and Implantation of the System of Quality (SQ); Accomplishment of a Pharmaceutical assay equivalence Pilot; Having been approved qualified for the ANVISA in day 22/06/2004. For the study pilot the Oxcarbazepine medicine was used for the pharmaceutical equivalence pilot and had been analyzed the following parameters: Hardness, Disintegration, Identification, Dissolution and Profile of dissolution getting resulted favorable in all the tests. It is concluded then to be pharmaceutical equivalents the analyzed medicines has tested and reference demonstrating that the laboratory meets apt to carry through the analyses the one that if destines.